Genèse : (genesis) [videorecording (DVD)] - Abita, Noée; Funk, Pier-Luc; Lesage, Philippe; Tremblay-Grenier, Édouard (Film Movement series., 2019)
Three teenagers are shaken up by their first loves in the turmoil of their youth. At a time when others are conforming, they stand their ground and assert their right to love and be free.